Serial-Refine Method for Fast Wake-Steering Yaw Optimization. Issue 3 (1st May 2022) - Fleming, Paul A.; Stanley, Andrew P. J.; Bay, Christopher J.; King, Jennifer; Simley, Eric; Doekemeijer, Bart M.; Mudafort, Rafael
Abstract: In this paper we present the Serial-Refine method for quickly finding the optimal yaw angles in wake steering. The method optimizes turbine angles serially from upstream to downstream using a small number of candidate angles. The presented results show that Serial-Refine finds solutions that are at least as good as former conventional optimization approaches but that require much less computation time.